The anticipated will in the law of palliative care, strength of the relation patient – Doctor - Sánchez Salazar, Diana Vanessa (2023)
In Colombia the 1733 Act of 2014 introduced the concept of advance directives, which in terms of its article 5. 4, the person capable, in healthy or disease state, voluntarily and in full possession of their legal and mental faculties, will express in a document the decisions regarding acceptance or rejection of specific medical treatment in case of crossing a chronic, terminal, irreversible or degenerative illness, and the accompaniment that will need in that moment. Similarly, the person can also establish the willingness or not to donate organs upon death. This publication pretend to help establish this advance directive document as a instrument of Biolaw for strengthening the doctor–patient relationship to bring back the therapeutic alliance model currently impaired.